Braid moves in commutation classes of the symmetric group. (May 2017) - Schilling, Anne; Thiéry, Nicolas M.; White, Graham; Williams, Nathan
Abstract: We prove that the expected number of braid moves in the commutation class of the reduced word ( s 1 s 2 ⋯ s n − 1 ) ( s 1 s 2 ⋯ s n − 2 ) ⋯ ( s 1 s 2 ) ( s 1 ) for the long element in the symmetric group S n is one. This is a variant of a similar result by V. Reiner, who proved that the expected number of braid moves in a random reduced word for the long element is one. The proof is bijective and uses X. Viennot's theory of heaps and variants of the promotion operator. In addition, we provide a refinement of this result on orbits under the action of even and odd promotion operators. This gives an example of a homomesy for a nonabelian (dihedral) group that is not induced by an abelian subgroup. Our techniques extend to more general posets and to other statistics.